Analysis of State Civil Apparatus Understanding of Zakat as a Deduction for Taxable Income - Handayani, Desi; Ananto, Rangga Putra; Qodri, Chelvin (Publication Division of International Ecsis Association, 2023)
There are still many people who do not know the role and position of zakat in income tax, that zakat can actually reduce taxable income provided that payments are made to zakat recipient institutions that have been determined and authorized by the government as stipulated in Government Regulation Number 60 of 2010. This study aims to determine how State Civil Apparatus (ASN) lecturers in the Politeknik Negeri Padang (PNP) understand zakat as a reduction in taxable income. The research method used is a survey with a qualitative approach. The population in this study were ASN lecturers at PNP. The sampling technique was carried out using the quota sampling method with 83 respondents. The data collection in this study was to conduct open interviews directly to ASN lecturers at PNP. The data was processed with a qualitative descriptive approach. The results showed that the majority of respondents did not know and understand about zakat as a deduction for taxable income and most respondents paid zakat not to official state institutions. It is hoped that the results of this study can be used by respondents in managing their zakat and taxes, and for policy makers to consider zakat not only as a deduction from taxable income but as a deduction from gross income in the calculation of personal tax and socialize the regulations that have been set.